TRANSPORTATION OF THE RF SPECTRA OVER FIBER: A WORKING SYSTEM - Moore, Jeanne (International Foundation for Telemetering, 2000)
International Telemetering Conference Proceedings / October 23-26, 2000 / Town & Country Hotel and Conference Center, San Diego, California === This paper presents the results of installing a distributed feedback (DFB) laser transmitter and the appropriate optical receiver in an operational site. Frequencies from 1435 to 2400 megahertz are transported intact from a remote site to a local site. From the theoretical calculations, 10 dB of dynamic range may need to be recovered by the use of an automatic gain circuit. The actual device is a delight, needing no additional circuitry to meet specifications. Predictions of performance were made from calculations. The installed system was measured for 1 dB compression point and for figure of merit.